1975
DOI: 10.1172/jci108117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen exposure on in vitro function of pulmonary alveolar macrophages.

Abstract: A B S T R A C T Bacterial infection may complicate pulmonary oxygen (02) toxicity, and animals exposed to high 02 concentrations show depressed in vivo pulmonary bacterial inactivation. Therefore, in vitro studies were undertaken to define the mechanism by which 02 alters pulmonary antibacterial activity. Normal and BCG pretreated rabbits were exposed to 100% 02 for 24, 48, and 72-h periods. Pulmonary alveolar macrophages (PAM) were obtained from the experimental animals and from nonoxygen exposed controls by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Although HBO has been shown to enhance some aspects of host defense, its overall effect appears to be immunosuppressive [39]. More specifically, HBO can impair macrophage function [40]. In this study, we found decreased deposits of macrophages over the injured nerve treated with HBO alone or combined with AFS treatment.…”
Section: Discussionsupporting
confidence: 45%
“…Although HBO has been shown to enhance some aspects of host defense, its overall effect appears to be immunosuppressive [39]. More specifically, HBO can impair macrophage function [40]. In this study, we found decreased deposits of macrophages over the injured nerve treated with HBO alone or combined with AFS treatment.…”
Section: Discussionsupporting
confidence: 45%
“…Although HBO has been shown to enhance some aspects of host defence, its overall effect appears to be immunosuppressive [6]. More specifically, HBO impairs macrophage function [7].…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effects of oxygen on phagocytic cells in vitro are well documented (1,17,18). In the animal this may be related to the intracellular reduction of oxygen to superoxide (0,) and H,02, both of which have been suggested as key factors in the bactericidal activity of phagocytes (19).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of prolonged exposure to oxygen on the immune response of animals or human beings have apparently not been investigated despite the repeated observations that several functions of the leukocyte and macrophage are inhibited when these cells are maintained in oxygen-rich atmospheres in vitro (1,2). It has recently been found that exposure of rodents to tolerable pressures of hyperbaric oxygen (HBO) markedly alters a diverse set of inflammatory, cell-mediated disease processes.…”
mentioning
confidence: 99%